2020
DOI: 10.48550/arxiv.2012.05096
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is $X(7200)$ the heavy anti-quark diquark symmetry partner of $ X(3872)$?

Ming-Zhu Liu,
Li-Sheng Geng

Abstract: The D ( * ) Ξ ( * )cc system can be related to the D ( * ) D( * ) system via heavy anti-quark

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 93 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…In Ref. [94], it was suggested that the structure around 7.2 GeV which was named as X(7200) can be related to χ c1 (3872) (formerly known as X(3872)) via heavy anti-quark di-quark symmetry. Orbital angular momentum addition to our calculation for 3S cccc tetraquarks could yield a candidate for X(7200).…”
Section: B Tetraquarksmentioning
confidence: 99%
“…In Ref. [94], it was suggested that the structure around 7.2 GeV which was named as X(7200) can be related to χ c1 (3872) (formerly known as X(3872)) via heavy anti-quark di-quark symmetry. Orbital angular momentum addition to our calculation for 3S cccc tetraquarks could yield a candidate for X(7200).…”
Section: B Tetraquarksmentioning
confidence: 99%
“…The existence of such multiplets of hadronic molecules not only enriches the hadron 0123456789(). : V,-vol spectrum, but also can help verify the molecular nature of some exotic states [42,43].…”
Section: Introductionmentioning
confidence: 99%